2019
DOI: 10.3390/su11082367
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Greenhouse Gas Emissions Produced by Road Projects in Abu Dhabi, United Arab Emirates

Abstract: Assessing the current levels of greenhouse gas (GHG) emissions from road transportation projects allows for benchmarking and is essential for potential emissions reduction. The objective of this study was to estimate the GHG emissions associated with the construction and operation of three road cases—two primary roads and one secondary road network—in Abu Dhabi, United Arab Emirates. The GHG emissions produced by the study cases were estimated using the RoadCO2 estimation tool. Results showed that the total em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…While GHG in general are transboundary and a global issue by nature, communities in the U.S. border region are directly impacted by vehicular emissions due to cross-border trade that is not prevalent in interior communities. Along this same line of research, Alzard et al [73] found that in 2016 the transport sector was responsible for the second largest amount of GHG emissions and that road transport was projected to continue to grow. Thus, as Pindyck [74] asks, after a cost benefit analysis of implementing an environmental policy, is a climate policy even worth adopting?…”
Section: Discussionmentioning
confidence: 92%
“…While GHG in general are transboundary and a global issue by nature, communities in the U.S. border region are directly impacted by vehicular emissions due to cross-border trade that is not prevalent in interior communities. Along this same line of research, Alzard et al [73] found that in 2016 the transport sector was responsible for the second largest amount of GHG emissions and that road transport was projected to continue to grow. Thus, as Pindyck [74] asks, after a cost benefit analysis of implementing an environmental policy, is a climate policy even worth adopting?…”
Section: Discussionmentioning
confidence: 92%
“…They found that emission factors were higher on-road compared to laboratory conditions and highest particle emissions were observed on-road during accelerations and engine braking. Other studies studied the influence of construction sites on air quality and focused on the estimation of emissions from road construction [9,[19][20][21]. Mulenski et al [22] investigated on PM 2,5 and PM 10 emission factors to assess emission inventories for the main construction activities.…”
Section: Introductionmentioning
confidence: 99%
“…GHG emissions on the construction stage are generated from the materials and equipment used. GHG emissions from primary road supply cause around 80% due to material consuming [3]. Roads constructed with the characteristic of a 1kilometer length and typical 2-lane roads with flexible pavement spend 6 TJ (tera joule) of energy [4].…”
Section: Introductionmentioning
confidence: 99%